La France de Makine : la France en migration - Harmath, Erzsébet (Verbum – Analecta Neolatina, 2008)
Pointing to various movements of individuals, the theme of migration-immigration-émigration 'migration-immigration-emigration' stimulates heterogeneous readings. The word migration, deriving from Latin migratio, meaning 'displacement from one country to another, to settle'. Human migration refers to the displacement of the place of life of the individual. The prefixes im- and é- are indicative of disparate movements. I will uncover the meaning of these three words, migration-immigration-emigration. I will analyze the shape of the idea of migration in literature, in this case an essay type, in order to clarify his a;nity with the notion of rhizome borrowed from Gilles Deleuze. After a thorough analysis of the essay rhizomatique, in the second part I will tackle the question of the image 'migrant' by Andrei Makine, a francophone writer who emigrated from Russia in the late 1980's.